Artificial Intelligence and other Speculative Metaphors - Blythe, Mark; Lindley, Siân; Murray-Rust, Dave (Proceedings of the 2025 ACM Designing Interactive Systems Conference, 2025)
The paper proposes “speculative metaphors” as constructs for reframing and critically engaging with ideas of artificial intelligence. It identifies a broad range of AI metaphors in the wider culture and technical literature and discusses metaphor design in terms of explanation, persuasion and speculation. To explore different metaphor design strategies, we use a custom GPT to generate a large number of variants on the “artificial intelligence” metaphor. The paper contributes a conceptual framing for such speculative metaphor drawing on ideas of knowledge and understanding, fusion and synthesis, collaboration and collectives. We argue that generating speculative metaphors provides a means of thinking critically about human-AI interaction.